Influence of the combination of SGLT2 inhibitors and GLP-1 receptor agonists on eGFR decline in type 2 diabetes: post-hoc analysis of RECAP study - Muta, Yoshimi; Kobayashi, Kazuo; Toyoda, Masao; Tone, Atsuhito; Suzuki, Daisuke; Tsuriya, Daisuke; Machimura, Hideo; Shimura, Hidetoshi; Takeda, Hiroshi; Yokomizo, Hisashi; Takeshita, Kei; Chin, Keiichi; et al. (Frontiers in Pharmacology, 2024)
Accumulating evidence has demonstrated that both SGLT2 inhibitors (SGLT2i) and GLP-1 receptor agonists (GLP1Ra) have protective effects in patients with diabetic kidney disease. Combination therapy with SGLT2i and GLP1Ra is commonly used in patients with type 2 diabetes (T2D). We previously reported that in combination therapy of SGLT2i and GLP1Ra, the effect on the renal composite outcome did not differ according to the preceding drug. However, it remains unclear how the initiation of combination therapy is associated with the renal function depending on the preceding drug.In this post hoc analysis, we analyzed a total of 643 T2D patients (GLP1Rapreceding group, n=331; SGLT2i-preceding group, n=312) and investigated the differences in annual eGFR decline. Multiple imputation and propensity score matching were performed to compare the annual eGFR decline. The reduction in annual eGFR decline in the SGLT2i-preceding group (pre: -3.5±9.4 ml/min/1.73 m 2 /year, post: -0.4±6.3 ml/min/1.73 m 2 /year, p<0.001), was significantly smaller after the initiation of GLP1Ra, whereas the GLP1Ra-preceding group tended to slow the eGFR decline but not to a statistically significant extent (pre: -2.0±10.9 ml/min/1.73 m 2 /year, post: -1.8±5.4 ml/min/1.73 m 2 /year, p=0.83) after the initiation of SGLT2i.After the addition of GLP1Ra to SGLT2i-treated patients, slower annual eGFR decline was observed. Our data raise the possibility that the renal benefits-especially annual eGFR decline-of combination therapy with SGLT2i and GLP1Ra may be affected by the preceding drug.